Effects of Yb/Tm Concentration and Pump Wavelength on the Performance of Ytterbium-Sensitized Thulium-Doped Fiber Laser - Damanhuri, S.S.A.; Halder, A.; Paul, Mukul Chandra; Ali, S.M.M.; Saidin, N.; Harun, Sulaiman Wadi; Ahmad, Harith; Das, S.; Pal, M.; Bhadra, S.K. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
A 1901.6-nm laser is demonstrated using the newly developed double-clad ytterbium-thulium-doped fiber (YTDF) samples in conjunction with 931-nm pumping through the transition of thulium ion from 3F4 to 3H6 with the assistance of ytterbium to thulium-ion energy transfer. The YTDF used was drawn from a D-shape preform, which was fabricated using the modified chemical vapor deposition and solution-doping technique. The laser operates at 1901.6 nm with an efficiency of 2.47% using 2-m-long YTDF in a Fabry-Pérot cavity with two fiber Bragg gratings. It is found that the higher ytterbium-to-thulium concentration ratio contributes to more efficient energy transfer between the sensitizer and acceptor ions in YTDF, which in turn lowers the threshold of the proposed ytterbium-thulium-doped fiber laser (YTFL). The lowest threshold pump power of the proposed YTFL is around 961 mW. The use of multimode pump with a wavelength slightly lower than 931 nm is also observed to improve both the laser's threshold and efficiency of the YTFL.